ANALISIS BIBLIOMETRIK HUBUNGAN LEARNING MANAGEMENT SYSTEM, FLIPPED CLASSROOM DAN GAMIFIKASI - Lobo, Elizabeth; Kurniawan, Citra; Fajarianto, Otto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The digital transformation in education has driven the massive adoption of innovative learning technologies and strategies. Learning Management System (LMS) is now the main infrastructure, which is often combined with Flipped Classroom strategy to reverse the traditional teaching method. On the other hand, Gamification is integrated to increase students’ motivation and engagement in the digital ecosystem. Despite its popularity, the conceptual map and research trends connecting these three domains have not been comprehensively identified. Therefore, this study aims to identify the research development trends and analyze the relationship structure between LMS, Flipped Classroom, and Gamification. This study uses a bibliometric analysis method on 200 articles from the Scopus database (2015-2025), which were analyzed using VOSviewer, Biblioshiny, and Publish or Perish. The results of the analysis show a significant increase in publication and citation trends in all three topics, indicating a growing academic interest. Further network mapping analysis reveals a strong symbiotic relationship: LMS serves as the technological foundation, Flipped Classroom as its main pedagogical application, and Gamification as a strategic layer to increase engagement within the framework. The conclusion of this study confirms that the integration of the three has formed a dominant paradigm in the digital education literature, providing guidance for practitioners and direction for future research. ABSTRAKTransformasi digital dalam pendidikan telah mendorong adopsi teknologi dan strategi pembelajaran inovatif secara masif. Learning Management System (LMS) kini menjadi infrastruktur utama, yang sering kali dikombinasikan dengan strategi Flipped Classroom untuk membalik metode pengajaran tradisional. Di sisi lain, Gamifikasi diintegrasikan untuk meningkatkan motivasi dan keterlibatan siswa dalam ekosistem digital tersebut. Meskipun populer, peta konseptual dan tren riset yang menghubungkan ketiga domain ini belum teridentifikasi secara komprehensif. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi tren perkembangan riset dan menganalisis struktur hubungan antara LMS, Flipped Classroom, dan Gamifikasi. Studi ini menggunakan metode analisis bibliometrik terhadap 200 artikel dari basis data Scopus (2015-2025), yang dianalisis menggunakan VOSviewer, Biblioshiny, dan Publish or Perish. Hasil analisis menunjukkan tren publikasi dan sitasi yang meningkat signifikan pada ketiga topik, menandakan minat akademis yang terus tumbuh. Analisis pemetaan jaringan lebih lanjut mengungkap adanya hubungan simbiosis yang kuat: LMS berfungsi sebagai fondasi teknologi, Flipped Classroom sebagai aplikasi pedagogis utamanya, dan Gamifikasi sebagai lapisan strategis untuk meningkatkan keterlibatan dalam kerangka tersebut. Simpulan penelitian ini menegaskan bahwa integrasi ketiganya telah membentuk sebuah paradigma dominan dalam literatur pendidikan digital, memberikan panduan bagi praktisi dan arah bagi riset di masa depan.